2022
DOI: 10.3390/foods11142026
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antioxidant Profile of Sorghum (Sorghumbicolor (L.) Moench) and Pearl Millet (Pennisetumglaucum (L.) R.Br.) Grains Cultivated in the Far-North Region of Cameroon

Abstract: Sorghum and pearl millet are grain crops that can grow in semi-arid climates, with nutritional and bioactive properties superior to those of major cereals such as rice, wheat, and maize. However, these properties vary a lot, depending on the genetic factors, growing conditions, and place of cultivation. Four sorghum and two pearl millet grains cultivars grown in the Far-North region of Cameroon were screened for their chemical composition and antioxidant profile. The proximate and mineral analyses were perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 46 publications
6
21
1
Order By: Relevance
“…Previous studies recorded the antioxidant activity of sorghum and moringa leaf flour. Yellow sorghum exerted 86.43% antioxidant activity against 0.1 M DPPH radicals [25], while moringa leaf flour 28.2% against 0.1 47 mM DPPH radicals [26].…”
Section: Figurementioning
confidence: 99%
“…Previous studies recorded the antioxidant activity of sorghum and moringa leaf flour. Yellow sorghum exerted 86.43% antioxidant activity against 0.1 M DPPH radicals [25], while moringa leaf flour 28.2% against 0.1 47 mM DPPH radicals [26].…”
Section: Figurementioning
confidence: 99%
“…The highest antioxidant activity against DPPH was determined in yellow-pale sorghum (87.71%), followed by red sorghum (81.15%). The above study [ 38 ] found higher amounts of PCs in sorghum than in pearl millet. Polyphenols are the main bioactive compounds of sorghum and are present in all varieties of this cereal crop.…”
Section: New Sources Of Phenolic Compoundsmentioning
confidence: 88%
“…Red sorghum grains showed high phenolic and antioxidant activities in vitro. Similarly, Mawouma et al [ 38 ], comparing different varieties of sorghum and millet, found that red sorghum contained the highest amounts of total polyphenols (82.22 mg GAE∙g −1 DM), total flavonoids (23.82 mg QE∙g −1 DM) and total 3-deoxyanthocyanidin (9.06 mg∙g −1 DM). The highest antioxidant activity against DPPH was determined in yellow-pale sorghum (87.71%), followed by red sorghum (81.15%).…”
Section: New Sources Of Phenolic Compoundsmentioning
confidence: 94%
See 1 more Smart Citation
“…Te commonly used fortifcants are fruits, vegetables, and even tubers [21][22]. It is therefore possible to use a fortifer containing an activator of the bioaccessibility of iron and zinc, in food products rich in these trace elements, such as pearl millet [23]. β-carotene is an activator of the bioaccessibility of iron and zinc [24] with the advantage of being efcient at high pH and in the presence of signifcant amounts of antinutritional factors [25,26].…”
Section: Introductionmentioning
confidence: 99%